Innovative Enterprises Development and Employees’ Knowledge Sharing Behavior in China: The Role of Leadership Style - Jiang, Daokui; Chen, Zhuo (Frontiers in Psychology, 2021)
Leadership is generally considered helpful for team knowledge sharing. However, differences in the influence of different leadership styles on team knowledge sharing mechanism is still unclear. To understand different leadership style foster team knowledge sharing, this study focuses on leader–follower trust during team interactions. From the perspective of leadership as social problem solving, we argue that transformational leadership and authoritative leadership are different linked to team knowledge sharing. Through the collection of a sample of 791 valid questionnaires in China, we used the structural equation model to test the theoretical model. Results showed that transformational leadership was positively linked to explicit and implicit knowledge sharing, while authoritative leadership was positively linked to explicit knowledge sharing. This positive relationship between authoritative leadership and knowledge sharing was mediated by trust tendency. Moreover, supportive culture and bureaucratic culture moderates the influence of trust tendency on implicit knowledge sharing. The moderating effect is embodied in the fact that the trust tendency has a greater impact on implicit knowledge sharing under the low-quality of supportive culture and the high-quality of bureaucratic culture. Finally, The study's implication for theory and practice were discussed, its limitations were identified, and directions for future research were suggested.